2007
DOI: 10.1371/journal.pone.0000302
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Regulatory Loop between foxi3a and foxi3b Is Essential for Specification and Differentiation of Zebrafish Epidermal Ionocytes

Abstract: BackgroundEpidermal ionocytes play essential roles in the transepithelial transportation of ions, water, and acid-base balance in fish embryos before their branchial counterparts are fully functional. However, the mechanism controlling epidermal ionocyte specification and differentiation remains unknown.Methodology/Principal FindingsIn zebrafish, we demonstrated that Delta-Notch-mediated lateral inhibition plays a vital role in singling out epidermal ionocyte progenitors from epidermal stem cells. The entire e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
208
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(224 citation statements)
references
References 82 publications
15
208
1
Order By: Relevance
“…For double-label in situ hybridization, igfbp5a, 14 trpv5/6, 11 and atp6v1al 17 riboprobes were labeled with either DIG or dinitrophenol following the published protocol. 55 Fluorescent images were acquired using a Leica TCS SP5 confocal microscope with the Leica LAS AF software.…”
Section: Discussionmentioning
confidence: 99%
“…For double-label in situ hybridization, igfbp5a, 14 trpv5/6, 11 and atp6v1al 17 riboprobes were labeled with either DIG or dinitrophenol following the published protocol. 55 Fluorescent images were acquired using a Leica TCS SP5 confocal microscope with the Leica LAS AF software.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was also found that not all ECaC-expressing cells coexpressed both zPMCA2 and zNCX1b in zebrafish gill NaR cell populations (Liao et al, 2007), which may be analogous to trout PNA + cells (see below). Fish gill cells that express only one or two (never all) of the three major Ca 2+ transporters may be in the process of terminal differentiation as Hsiao and coworkers (Hsiao et al, 2007) reported in zebrafish embryonic skin ionocytes. Alternatively, the Ca 2+ transporter(s) expressed in these cells may be involved in intracellular Ca 2+ homeostasis or other cellular events (Prasad et al, 2007;Reppel et al, 2007), and this needs to be clarified in further investigations.…”
Section: Nar Cellsmentioning
confidence: 96%
“…Both cells are essential for human physiological processes, and malformation of them is associated with human diseases, including bronchiectasis, hydrocephalus and distal tubule acidosis 1,2 . Cell fate specifications of MCCs and ionocytes are known to be suppressed by the Notch pathway in various developing epithelia [5][6][7][8][9][10][11][12][13][14] . However, MCCspecific and ionocyte-specific transcriptional programmes are governed by different master regulators: a coiled-coil protein multicilin 15 and a forkhead transcription factor foxj1 (refs [16][17][18] for MCCs and another forkhead transcription factor foxi1 (refs 7-9,19-21) for ionocytes.…”
mentioning
confidence: 99%